Analysis of Bio-battery Making from Avocado Peel as an Alternative Practicum Design to Develop Pancasila Student Profile Character - Listiowati, Eni; Fikroh*, Retno Aliyatul; Milehman, Natthawat (Universitas Syiah Kuala, 2024)
The renewal of the curriculum from 2013 to the Merdeka curriculum emphasizes the importance of developing the characteristics of the Pancasila Student Profile in education through project-based learning, such as practicums. However, practicums on voltaic cell material often use expensive kits, while there is an alternative using bio-battery media from avocado peel waste, which is more environmentally friendly and economical. This research aims to utilize avocado peel waste as a substitute for commercial batteries, in the hope of reducing battery waste and providing an environmentally friendly and inexpensive practicum design, as well as building the characteristics of the pancasila student profile. The type of research used is descriptive qualitative, consisting of literature study, experimentation, and interview stages. The results showed variations in voltage and current strength produced by avocado peel bio-batteries depending on the variety of avocado peel and the length of fermentation time. Although the variation in avocado peel variety does not result in a significant difference, the electrical energy produced shows the potential of using this practicum in improving students' understanding and building the characteristics of the pancasila student profile.